BENIGN LYMPHANGIOENDOTHELIOMA - Aleksandr V. Patrushev; Irena E. Belousova; Tatiana A. Gorislavskaya; Aleksey V. Suharev; Aleksey V. Samtsov (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
The authors describe modern data relating to the definition, clinical, pathological and immunohistochemical features of a rare vascular tumor - benign lymphangioendothelioma. The problems of differential diagnosis with Kaposi's sarcoma and angiosarcoma are discussed. This is the first description of this tumorin domestic literature.